Analyzing the effects of the choice of model in the context of marginal changes in final demand - Reinout Heijungs; Arjan de Koning (Journal of Economic Structures, 2019)
Literature on the choice of model for deriving an input-output table (IOT) from a pair of supply-use tables (SUTs) has focused on the consequences for the IOT and the Leontief inverse. Analyzing the technology and fixed sales structure transformation models and their applications involving impact analysis and multipliers of factor inputs or environmental extensions, we prove that the product technology and fixed sales structure assumption models are effectively identical and so are the industry technology and fixed product sales structure models. A dimensional analysis shows that the product technology and fixed sales structure assumption models maintain consistency in accounting units, while the industry technology and fixed product sales structure models do not. Comparison with selected topics in environmental life cycle assessment (LCA) shows that the commodity technology and fixed industry sales structure models yield results that are compatible with mainstream LCA. We conclude these models are 'correct' in the context of impact analysis and multipliers of the satellite of a SUT/IOT system, despite the fact that they may result in 'negatives.' We propose a new quantity, the intensity matrix, and highlight its benefits in terms of the consistency of dimension and ease of interpretation. We illustrate our findings with examples of a SUT/IOT for several EU countries. We finally discuss briefly the possibility of calculating contributions to multipliers, where it is shown that models that are equivalent in terms of observable results (multipliers) disagree on unobservable quantities (contributions to multipliers).
Keywords: 330; Supply-use table (SUT); Input-output table (IOT); Choice of model; Multiplier; Life cycle assessment (LCA)